Ta‘limda fanlararo integratsiyani ta‘minlashda innovatsion ta‘lim texnologiyalardan foydalanish (ILIM hám JÁMIYET, 2023)
This article presents the effectiveness of the teaching methodology using innovative educational technologies in providing interdisciplinary integration of education.